Introductory chapter : Protection of materials - Canosa, Guadalupe (2017)
The science and technology of materials have as objective provided access to specific knowl- edge in this field and besides generated matters of interest for the development of original researches leading to new materials and, as a consequence, to proper protection methods to achieve high economic impact. Since iron and steels constitute a group of widely used materials in civil and industrial construction, this chapter describes firstly the fundamental concepts of metal corrosion and the most frequent failures originating on service. Besides, in this chapter, it was considered of interest to include aspects inherent to the physicochemistry of fire and its mechanism of spreading because of the significant human and material losses produced year after year by action of the fire. It is appropriate to mention that the different chapters of this book describe innovative methods of surface treatment to control the kinetics of metallic corrosion and the action of fire on several materials.